(untitled) (Jurnal Manajemen Perhotelan, 2012)
This research is going to analyze the influence of employee’s perception to the empowerment that has been done by the company towards employee turnover intention. Hotel X is one of the three stars hotels in Kupang, Nusa Tenggara Timur that is having the employee turnover problem. Based on the analysis, employee empowerment perception simultaneously gives influence on the employee turnover intention. However, out of the seven variables of employee empowerment, there are only five variables which significantly influence the turnover intention; while the other two variables do not give a significant influence on the turnover intention. Moreover, meaningfulness is the most dominant variable in giving influence on the employee turnover intention.